MODERNIZING THE HIGHER EDUCATION SYSTEM THROUGH DIGITAL TECHNOLOGIES: AN ANALYSIS OF ECONOMIC EFFICIENCY - Abduganiyeva Mavjuda Asatulayevna; Anvarova Muqaddas Mahammadjanovna; Mirziyodova Gulnozakhon ayubkhon qizi (Modern American Journals, 2025)
This article systematically analyzes the relationship between the quality of education and economic efficiency through the introduction of digital technologies in the higher education system. It shows how the formation of modern digital infrastructure, tools for automating educational processes, distance learning platforms (LMS) and technologies based on artificial intelligence affect the creation of an effective educational environment in higher education institutions. The article deeply studies how the quality of education has changed as a result of the introduction of digital technologies, such factors as the efficiency of resource use, cost reduction and activation of student activity. Using statistical indicators, tables and graphs, the above processes are analyzed based on real numbers, and the economic and scientific significance of digital transformation in the higher education system is
Keywords: Digital technologies, economic efficiency, digital transformation, LMS (Learning Management System), infrastructure investment, artificial intelligence, education quality, e-learning platforms.